Penerapan Eksperimen Sains Untuk Meningkatkan Kreativitas Anak Usia Dini 5-6 Tahun - Pratiwi, Sindi; Sit, Masganti (Jurnal Ilmiah Profesi Pendidikan, 2025)
The purpose of this study is to demonstrate how color mixing scientific experiment activities at RA An-Nida have improved the creativity of children ages 5 to 6.  The absence of use of science experiment activities in early childhood education and the lack of teacher-provided stimulation to foster children's creativity serve as the backdrop for this study.  Learning consequently frequently concentrates solely on reading and writing.  Eleven youngsters in group B:two boys and nine girls participated in this two-cycle classroom action research (CAR) study.  Four steps make up the research process: preparation, execution, observation, and reflection.  Observational methods were used to gather the data, which were then descriptively examined. From 0% in the initial condition to 63% in the first cycle and 100% in the second, the results demonstrated a notable rise in children's inventiveness.  It is clear that science experiment activities, especially color mixing, help kids between the ages of five and six become more creative.